Vulvar lichen sclerosus et atrophicus: Refractory to standard therapy - Thasneem S Luqman; Akshay Kalavant; K S Sunil Kumar; A R Swathy (Wolters Kluwer Medknow Publications, 2023)
Vulvar lichen sclerosus et atrophicus is an inflammatory disease which can affect the pediatric age group, although rarely. Its prevalence is underestimated. It may have genital or extragenital manifestations. If left untreated, it may progress to complications which hamper the quality of life. The treatment of choice is topical clobetasol propionate. Here, we present a case of prepubertal vulvar LS, which was refractory to topical clobetasol but responded to topical tacrolimus application.